Effects of Puddling Types and Rice Establishment Methods on Soil Characteristics and Productivity of Rice in Southern China - Evans Asenso; Zhimin Wang; Tian Kai; Jiuhao Li; Lian Hu (Applied and Environmental Soil Science)
Puddling is an important operation to minimize soil nutrient leaching and thereby increasing the availability of plant nutrients and achieving reduced soil condition. Good puddle field conditions are needed to create a favorable environment for normal growth of rice plants. However, long-term effects of puddling could lead to forms of large clods in fine textured soils, resulting in negative effect on the soil characteristics, preventing seed-soil contacts, and leading to decline in rice yield. This study was conducted in 2 years with treatment including puddling the land twice with moldboard plow and pregerminated seeds were hill-seeded with direct seeding machine (PD), puddling the land twice with rotary tiller and pregerminated seeds were hill-seeded with direct seeding machine (RD), puddling the land twice with moldboard plow and 15-day-old seedlings were hill-transplanted with transplant machine (PT), and puddling the land twice with rotary tiller and 15-day-old seedlings were hill-transplanted with transplant machine (RT) to assess the effects of puddling and rice establishment method on soil characteristics and rice yield. Results revealed significant improvement in the bulk density and increase in SOC, N, P, and K in PD. The maximum microbial population was found in PD. Rice grain yield showed a higher productivity increase of 7.65 t·ha−2 (31.25%) and 3.93 t·ha−2 (13.91%) for 1H and 2H (1H: 1st harvest and 2H: 2nd harvest), respectively, in PD compared with the lowest of 5.76 t·ha−1 and 3.45 t·ha−1 in 1H and 2H, respectively, under RT. Overall, PD was found to be the most suitable puddling type and rice establishment method for soil improvement and increasing rice yield.